PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN STRATEGI CTL DALAM PEMBELAJARAN SENI RUPA KELAS VII SMPN 14 SIJUNJUNG - YUSMI OKTA WINDA, Drs. Wisdiarman, M.Pd, Dra. Ernis, M.Pd (Serupa The Journal of Art Education, 2015)
This study aims to determine the difference result of student by using thelearning strategies contextual teaching and learning on subjects visual art class vii at SMPN 14 Sijunjung. The types of study is quasi experimental design with pretest-postest only control group design, determination of the sample using technic of purposive sampling on students class vii at SMPN 14 Sijunjung. The research findings suggest that, the results of t-test calculation obtained thitung =13.000 and ttabell =1.721 , so that thitung > ttabel so, HO is denied. It means the average (mean) of value experimental group and control group are not identical or different. So, we can conclude that the use of Contextual Teaching and Learning give possitive feed back to increasing the learning outcome the student class vii SMPN 14 Sijunjung on subjects visual art.Keynote: strategies CTL, learning outcome, visual art